Verification, Model Checking, and Abstract Interpretation 17th International Conference, VMCAI 2016, St. Petersburg, FL, USA, January 17-19, 2016. Proceedings - Jobstmann, Barbara; Leino, K. Rustan M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the 17th International Conference on Verification, Model Checking, and Abstract Interpretation, VMCAI 2016, held in St. Petersburg, FL, USA, in January 2016. The 24 full papers together with 2 invited talks and 1 abstract presented were carefully reviewed and selected from 67 submissions. VMCAI provides topics including: program verification, model checking, abstract interpretation and abstract domains, program synthesis, static analysis, type systems, deductive methods, program certification, debugging techniques, program transformation, optimization, hybrid and cyber-physical systems.
Abstract Interpretation -- Abstraction -- Hybrid and Timed Systems -- Dynamic and Static Verification -- Probabilistic Systems -- Concurrent Programs -- Parameterized and Component-Based Systems -- Solver Improvements.
Keywords: Computer science; Computer communication systems; Software engineering; Programming languages (Electronic computers).; Computers; Computer logic; Mathematical logic; Computer Science; Logics and Meanings of Programs; Software Engineering; Computer Communication Networks; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Programming Languages, Compilers, Interpreters; Electronic books